+0  
 
-1
74
1
avatar

Simplify \(\left(\dfrac{a(a+1)}{2}\right)^2-\left(\dfrac{a(a-1)}{2}\right)^2\)

 Jul 4, 2020
 #1
avatar+21953 
+1

Simplify:        [ a(a + 1) / 2 ]2  -  [ a(a - 1) / 2 ]2 

  =                  [ (a2 + a) / 2 ]2  -  [ (a2 - a) / 2 ]2​ 

  =            (a4 + 2a3 + a2) / 4  -  (a4 - 2a3 + a2​) / 4 

   =              [ (a4 + 2a3 + a2)  -  (a4 - 2a3 + a2​) ]  /  4

   =              [ a4 + 2a3 + a2 - a4 + 2a3 - a2 ] / 4

   =                                     4a3 / 4

   =                                         a3 

 Jul 4, 2020

13 Online Users

avatar